Konstruksi Barista Perempuan Sebagai Strategi Komunikasi Pemasaran di Coffe shop Kopimana27 - Maurilla Ariezka Aldha M (Kanal: Jurnal Ilmu Komunikasi, 2019)
The development of coffeeshop which is dominated by Barista Perempuan is a new development as a strategy that can be implemented in a coffee shop, one of which is Kopimana27 which raises the icon of women. The purpose of this study was to determine the construction of women's baristas as marketing strategies in Kopimana27 and to determine the role of baristas as marketing strategies in Kopimana27. This study uses qualitative methods and constructivist paradigms. The results of this study are Kopimana27 in conducting marketing strategy 4, namely product, place, price and promotion. Construction of Kopimana27 in its female Barista by presenting communicative and informative Barista to its customers, Kopista27 Barista must have knowledge of the Coffee shop according to the existing SOP. The role of barista women in Kopimana27 in increasing sales significantly with a positive response from loyal customers Kopimana. Dega thus, the specialty of Barista Kopimana27 is described as an icon in their flagship product, the wife's milk coffee.